THE IMPORTANCE OF SOME NEW CLINICAL INDICES IN THE EVALUATION OF CHILDHOOD OBESITY - Donma, Mustafa Metin; Donma, Orkide (LIFE: International Journal of Health and Life-Sciences, 2017)
Childhood obesity is a multisystem disease and associated with severe complications. Accurate evaluation requires difficult and detailed investigation. Therefore, assessment of anthropometric measurements and formulas as well as some ratios, is important. The aim of the study is to introduce an obesity index, which is capable of discriminating the children in different obesity grades. A total of two hundred and fifty children were included into the scope of the study. Anthropometric measurements and obesity classification were performed. Waist-to-height, head-to-neck ratios, body mass index (BMI), recently developed indices; “Diagnostic Obesity Notation Model Assessment” (DONMA) Index-I derived from weight and DONMA Index-II derived from fat mass were calculated. Upon evaluation of waist circumference, waist-to-height, head-to-neck ratios, no statistically significant difference was observed between groups. Strong correlations were found between BMI and DONMA Index-I as well as II in all groups. Overlapping patterns were observed for overweight and obese children for waist circumference, waist-to-height, head-to-neck ratios, BMI and DONMA Index-I. However, DONMA Index-II showed a clear-cut separation between groups; normal weight-overweight and overweight-obese.This study revealed that body ratios and formulas based upon body fat are more valuable parameters than those based on weight for the evaluation of obesity in children.